2022
DOI: 10.1002/ange.202205906
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origin of Enhanced Circularly Polarized Luminescence in Hybrid Manganese Bromides

Abstract: Chiral hybrid metal halides with a high dissymmetry factor (glum) and a superior photoluminescence quantum yield (PLQY) are promising candidates for circularly polarized luminescence (CPL) light sources. Here, we report eight new chiral hybrid manganese halides, crystallizing in the non‐centrosymmetric space group P212121 and showing intense CPL emissions. Oppositely‐signed circular dichroism (CD) and CPL signals are detected according to the R‐ and S‐configurations of the chiral alkanolammonium cations. Time‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Chiral perovskites are essential in the application of circularly polarized light (CPL) sources and spintronics. Chiral perovskites are constructed by incorporating chiral molecules into achiral inorganic perovskite framework, in which the chirality can transfer from molecules to perovskites and then chiroptical activity emerges. , Although significant progress has been made in CPL emission based on chiral perovskites, most of them are toxic lead-based perovskites, , which is harmful to human and environment and constrains their practical applications. Several groups have demonstrated CPL of lead-free chiral perovskites using hybrids of Mn, Cu, Sn, and so on. However, the highest degree of circular polarization (DOCP) of all the reported lead-free chiral perovskites is 0.5% to the best of our knowledge, which is due to all those lead-free chiral perovskites being dominated by self-trapped exciton (STE) emission, and thus the spin relaxation reduces DOCP dramatically . Although it has been observed that STE was absent in a Bi-based chiral perovskite, the chiroptical properties have not been investigated …”
mentioning
confidence: 97%
“…Chiral perovskites are essential in the application of circularly polarized light (CPL) sources and spintronics. Chiral perovskites are constructed by incorporating chiral molecules into achiral inorganic perovskite framework, in which the chirality can transfer from molecules to perovskites and then chiroptical activity emerges. , Although significant progress has been made in CPL emission based on chiral perovskites, most of them are toxic lead-based perovskites, , which is harmful to human and environment and constrains their practical applications. Several groups have demonstrated CPL of lead-free chiral perovskites using hybrids of Mn, Cu, Sn, and so on. However, the highest degree of circular polarization (DOCP) of all the reported lead-free chiral perovskites is 0.5% to the best of our knowledge, which is due to all those lead-free chiral perovskites being dominated by self-trapped exciton (STE) emission, and thus the spin relaxation reduces DOCP dramatically . Although it has been observed that STE was absent in a Bi-based chiral perovskite, the chiroptical properties have not been investigated …”
mentioning
confidence: 97%